1988
DOI: 10.1111/j.1432-1033.1988.tb14013.x
|View full text |Cite
|
Sign up to set email alerts
|

Structure and activity of trypsin in reverse micelles

Abstract: The kinetic properties of trypsin have been studied in reverse micelles formed by two surfactant systems, namely bis(2-ethylhexyl) sodium sulfosuccinate (AOT) in isooctane, and hexadecyltrimethyl ammonium bromide (CTAB) in chloroform/isooctane (1 : 1, by vol.). Three substrates have been used, namely W-benzoyl-L-Arg ethyl ester, N"-benzoyl-L-Phe-L-Val-L-Arg p-nitroanilide (BzPheValArg-NH-Np) in AOT and W-benzyloxycarbonyl-LLys p-nitrophenyl ester (ZLysO-Np) in CTAB. One of the main aims of the work was to comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
6

Year Published

1989
1989
2014
2014

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 73 publications
(41 citation statements)
references
References 38 publications
(14 reference statements)
2
33
0
6
Order By: Relevance
“…Also, there is substantial agreement with the values found in other micellar systems, e.g. in AOT/isooctane [29]. In the case of a-chymotrypsin, both K , and k,,, values are smaller than those found in water.…”
Section: Kinetic Studiessupporting
confidence: 74%
See 2 more Smart Citations
“…Also, there is substantial agreement with the values found in other micellar systems, e.g. in AOT/isooctane [29]. In the case of a-chymotrypsin, both K , and k,,, values are smaller than those found in water.…”
Section: Kinetic Studiessupporting
confidence: 74%
“…Several independent investigations have shown that the pH,,, as well as the general pH/activity profilc in AOT reverse micelles is very similar to that in water for both trypsin [29] and a-chymotrypsin [28]. Particularly in aqueous solution, the pH,,, for a-chymotrypsin and trypsin are 8.2 and 8.5, respectively, in aqueous solution.…”
Section: The P H Dependence Of the Enzymatic Activitymentioning
confidence: 98%
See 1 more Smart Citation
“…IA). The same has been found for trypsin [4]. This observation is a direct consequence of the drastic changes in k2 and K, observed upon solubilizing the enzyme in reverse micelles (see below).…”
Section: Results and Disussionsupporting
confidence: 52%
“…The variation of their radii from 0.5-13 nm is directly related to the waterhrfactant molecular ratio W,, (Bru et al, 1995). Many encapsulations of enzymes (achymotrypsin, lysozyme, myoglobin) in bis-(2-ethylhexyl) sodium sulfosuccinate surfactant have been reported (Walde et al, 1988 ;Perez-Gilabert et al, 1992). The strength of interactions between enzyme and surfactant can be modulated by the modification of the W,, ratio.…”
Section: Circular Dichroismmentioning
confidence: 99%